Forecasting of Future Medical Care Expenditure in Japan Using a System Dynamics Model - Sachie Inoue; Hua Xu; Jean-Claude Maswana; Makoto Kobayashi (SAGE Publishing, 2022)
Background The aim of this study was to construct a system dynamics (SD) model to estimate the future medical care expenditure and to address the dynamic issues of health care that should be resolved. In particular, the measures for promoting the spread of generic drug (GE drug) usage in Japan and reducing cancer-related medical expenses were investigated regarding their future impact on medical finances. Methods The SD model was constructed from FY 2018 to FY 2050. The change in the future GE drug quantity share was analyzed by using a regression equation. The impact of the increase in medical expense for cancer and the change in the future national medical care expenditure were also estimated. Results The annual total medical care expenditure in FY 2050 would arrive at 58.9-64.2 trillion JPY (US$ 535.1-584.0 billion) (1.3-1.5 times higher than that in FY 2018) with different trends in age groups. The cumulative total medical care expenditure was expected to decrease by about 787.0-989.4 billion JPY (US$ 7.2-9.0 billion) if the impact of the spread of GE drug usage was considered. On the other hand, due to the continuous increase in the cancer-related medical expense, the cumulative total medical care expenditure was estimated to increase about 7554.3-11715.0 billion JPY (US$ 68.7-106.5 billion). Conclusions If the cancer-related medical expense continues to increase in the future, an increase of 686.4-1104.2 billion JPY (US$ 6.2-10.0 billion) in FY 2050 is expected which suggests that this disease field should be prioritized regarding the measures to maintain medical finances.